The Effect Of Ability, Leadership, Motivation, Facilities, And Rewards On The Work Performance Of Employees In The Tanjung Enim Village Muara Enim Regency - Sri Haryani; Abdul Hamid; Delvina Yulanda (Utami Publisher, 2026)
The author's research aimed to determine and analyze the influence of ability, leadership, motivation, facilities, and rewards, individually and collectively, on the work performance of employees in Tanjung Enim Village, Muara Enim Regency. The research method used in this study was quantitative, using a questionnaire distributed to respondents. Data quality was tested using validity, reliability, and normality tests. The analysis used descriptive and inferential analyses using statistical calculations using multiple regression formulas, partial tests, simultaneous tests, and the coefficient of determination. The results showed that ability significantly influenced the work performance of employees in Tanjung Enim Village, Muara Enim Regency. Leadership significantly influenced the work performance of employees in Tanjung Enim Village, Muara Enim Regency. Motivation significantly influenced the work performance of employees in Tanjung Enim Village, Muara Enim Regency. Facilities had no significant effect on the work performance of employees in Tanjung Enim Village, Muara Enim Regency. Rewards significantly influenced the work performance of employees in Tanjung Enim Village, Muara Enim Regency. Ability, leadership, motivation, facilities, and rewards have a significant joint influence on the work performance of employees in Tanjung Enim Village, Muara Enim Regency.